The real Lolita : the kidnapping of Sally Horner and the novel that scandalized the world - Weinman, Sarah (Ecco, an imprint of HarperCollinsPublishers, 2018)
"In 1948, Sally Horner was just eleven years old when she was kidnapped by a man claiming to be an FBI agent. Seven years later, Vladimir Nabokov published Lolita, perhaps the most seminal novel of the twentieth century. Sarah Weinman's investigation into how the two are connected is a thrilling, heartbreaking mix of literary scholarship and true-crime writing."--back cover.